Cytomegalovirus (CMV) Infection in Infants: Two Case Reports and Review of Literature - Salmuna, Zeti Norfidiyati; Abdul Hamid, Norjihan; Awang@Ismail, Nabilah; Muhd Besari, Alwi; Mazlan, Mohd Zulfakar; Mohamad, Suharni (IIUM Medical Journal Malaysia, 2021)
Cytomegalovirus (CMV) is a virus under the Herpesviridae family. We describe two case reports on different manifestations of infants with CMV infection presented with neonatal jaundice, small for gestational age (SGA) and congenital cataract. Congenital CMV (cCMV) was diagnosed in a neonate presented with jaundice and SGA. cCMV cannot be excluded in another case as no CMV PCR done within 3 weeks of life. Only one cCMV infection was treated with 6 weeks of ganciclovir anti-viral therapy, which presented with neonatal jaundice, SGA with a very high CMV viral load. All cases were under multidisciplinary follow[1]up, including pediatric for developmental assessments, audiologist for hearing assessment, and ophthalmology for vision assessment. These case reports describe the importance of thorough clinical examination and early screening of CMV infection in infants to rule out cCMV as CMV is the commonest congenital treatable viral infection in Malaysia. Early treatment and intervention can be planned for child wellbeing.